Estrategia de manejo de recursos ecosistémicos marinos costeros del Caribe Sur de Costa Rica orientada a la adaptación a la variabilidad climática de las comunidades costeras - Piedra-Castro, Lilliana María (Instituto Tecnológico de Costa Rica, 2017)
The composition and structure of shallow coral reefs community allow the conservation evaluation of these ecosystems which are priorities of protection at the coastal—marine biodiversity and local economies. The objective of this study was to known the composition and the structure of shallow coral reefs communities in 4 South Caribbean Coast locations in Costa Rica in order to propose conservations measures. The investigation took place at lsla Uvita, Parque Nacional Cahuiha (PNC), Puerto Viejo and Refugio Nacional de Vida Silvestxc Gandoca Manzanillo (REGAMA). Between 2011 and 2012 AGRRA methodology was applied with his modified version 22 in a deepness l to 6 m: likewise the percentage of coverage was made for live corals, marine grass bed, macro algae and the background bare grouped the rocks, mud, sand and the number of sea urchin. Ecosystem analysis was done through the Shapiro-Wilks and Levene tests, the Jackknife, t- Student testing’s, the Pielou evaluation rates and Berger-Parker analyze with the conglomerates analysis and the principal components classifiwtions by sites and species As a result, 30 different species of coral were identified corresponding to 15 families; where Faviidae family is the most representative. It was also identified 20 species of macro algae belonging to 9 families that have major coverage in Pueno Viejo and less in REGAMA. Two species of marine phanerogams were identifying and they presents major coverage in REGAMA and less coverage in lsla Uvitac On the other hand, the major and less coverage of coral was registering in lsla Uvita and Puerto Viejo respectively, while the protective areas present similar coverage, The most abundant species of sea urchin was Diadema antiliarum, whose densities were higher in REGAMA and lower in PNC. Including the composition and structure of the shallow coral reefs community of the 4 locations evaluated for the South Caribbean, goes from regular in Puerto Viejo to good in lsla Uvita.
Tesis (Doctorado en Ciencias Naturales para el Desarrollo con énfasis en Gestión de las Recursos Naturales) Instituto Tecnológico de Costa Rica. Universidad Nacional de Costa Rica. Universidad Estatal a Distancia, Doctorado en Ciencias Naturales para el desarrollo, 2017.
Keywords: Biodiversidad; Ecosistemas marinos; Cambio climático; Uso del suelo; Conservación; Arrecifes coralinos; Research Subject Categories::NATURAL SCIENCES